2018
DOI: 10.1186/s12871-018-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face intubation using a lightwand in a patient with severe thoracolumbar kyphosis: a case report

Abstract: BackgroundSevere deformity of the thoracolumbar spine may cause difficulty in airway management during induction of anesthesia. Therefore, special attention must be devoted to patient safety.Case presentationA 65-year-old male with severe thoracolumbar kyphosis was scheduled to undergo posterior spinal fusion under general anesthesia. Due to his inability to lie supine, conventional tracheal intubation under direct laryngoscopy was difficult. Alternatively, face-to-face tracheal intubation using a lightwand in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…[424][425][426][427][428] Case reports observed successful intubations with lighted and optical stylets (Category B4-B evidence). [429][430][431][432][433][434][435][436][437] Rigid bronchoscopes. The literature is insufficient to evaluate the benefit or harm of the rigid bronchoscope for patients with anticipated difficult airways.…”
Section: Practice Guidelines For Difficult Airway Managementmentioning
confidence: 99%
“…[424][425][426][427][428] Case reports observed successful intubations with lighted and optical stylets (Category B4-B evidence). [429][430][431][432][433][434][435][436][437] Rigid bronchoscopes. The literature is insufficient to evaluate the benefit or harm of the rigid bronchoscope for patients with anticipated difficult airways.…”
Section: Practice Guidelines For Difficult Airway Managementmentioning
confidence: 99%
“…[ 9 ] Glottic visualization is easier in the sitting position due to the tendency of the tongue to fall into the inferior oral cavity, not posteriorly to the oropharynx. Comparison studies on airway mannequins[ 10 ] and cadavers[ 11 ] positioned upright have shown statistically insignificant differences in first-pass success and intubation time. In the present case, the advantages of having the patient sitting upright are more pronounced, as his shredded tongue would have been more difficult to displace with the laryngoscope blade.…”
Section: Discussionmentioning
confidence: 99%
“…The skill of face-to-face intubation enables airway management in a patient in an unusual position not only in bariatric procedures. [3] Another point to discuss is using a video laryngoscope with a channel (a channeled blade) which might be a facilitation of an intubation technique. It is difficult to define how important using the channeled blade was regarding the face-to-face method for results of the study.…”
Section: Discussionmentioning
confidence: 99%
“…spondyloarthritis), the intubation efforts performed by a person standing in front of a patient might be the only option for successful airway management. [1][2][3] In case of general anesthesia in morbidly obese patients with body mass index over 40 kg m −2 , the face-to-face method may be considered as the patient is placed in head-elevated laryngoscopy position with the upper body elevated. Such an approach is recommended in this group of patients.…”
Section: Introductionmentioning
confidence: 99%